Comparison of two classifications of cavity preparations and carious lesions: Mount & Hume, and Black - Alain Manuel Chaple Gil (Editorial Ciencias Médicas, 2015)
Introduction: in dental practice it is common to find professionals who do not know or are unable to apply Mount & Hume's cavity preparation classification. Information about the subject is scarce in the literature published in Spanish, despite the fact that leading dental institutions worldwide consider it to have current validity. Objective: compare Mount & Hume's classification of dental cavity preparations as modified by Lasfargues and colleagues, with Black's. Methods: a bibliographic review was conducted of papers about Mount & Hume's classification of cavity preparations published from 2006 to 2014. The review included high impact online journals from the databases Google Scholar, Scopus, Scielo, Hinari and Medline. The search terms used were "new cavity classification", "cavity design", "preservation and restoration of tooth structure", "enamel remineralization", "Mount Hume Lasfargues Classification". The 163 papers obtained were scanned, but the study was restricted to the 52 which dealt with the topic in a more comprehensive manner. Data analysis and integration: black's classification was considered to be insufficient in the light of the new technologies and current concepts about minimally invasive therapies. Mount & Hume's classification shows the limitations of Black's preparations. Final considerations: black's classification had limitations with relation to Mount & Hume's and Lasfargues'. Both classifications should coexist and it is feasible to apply them in current conservative dental practice.